Noninvasive evaluation of vaginal fibrosis following radiotherapy for gynecologic malignancies: A feasibility study with ultrasound B‐mode and Nakagami parameter imaging. Issue 2 (9th January 2013) - Yang, Xiaofeng; Rossi, Peter; Bruner, Deborah Watkins; Tridandapani, Srini; Shelton, Joseph; Liu, Tian
Abstract : Purpose: : This study's purpose is to develop a quantitative ultrasound technology to evaluate radiation‐induced vaginal fibrosis. Radiation therapy (RT) is an important treatment modality for most gynecologic (GYN) malignancies. However, vaginal fibrosis is a common chronic side‐effect, affecting 80% of women post vaginal or pelvic RT. Vaginal fibrosis leads to pain, sexual dysfunction, and poor quality of life. Methods: : The authors propose a novel ultrasound approach that combines conventional B‐mode imaging with Nakagami parameter imaging to quantitatively evaluate post‐RT vaginal injury. From the B‐mode image, vaginal wall thickness and echo intensity were calculated to capture the anatomy and echogenicity of the vaginal wall. From Nakagami imaging, two statistical parameters, Nakagami probability density function (PDF) and Nakagami shape, were computed to measure the concentration and arrangement of vaginal tissue microstructures. This novel ultrasound imaging concept was investigated in a pilot study of 12 patients, who were previously diagnosed and treated for endometrial cancer. The 12 participants were stratified into two groups: (1) the control group consisted of 6 patients who received surgery (hysterectomy) alone and (2) the post‐RT group consisted of 6 patients who received surgery plus radiotherapy, with a follow‐up time of 12–38 months. Each participant underwent one transvaginal ultrasound study (6 MHz). Three transverse images of the anterior vaginal wall were acquired in a 2 cm step from the apex (vaginal cuff) to the introitus (vagina opening). The vaginal wall thickness, echo intensity, Nakagami PDF, and Nakagami parameter were calculated to evaluate radiation‐induced vaginal fibrosis. Results: : Both B‐mode and Nakagami methods showed significant differences in parameters between the post‐RT and nonirradiated vaginal walls. Compared with the control group, the vaginal wall thickness of the post‐RT group increased by 153.2% ( p = 0.002), the echo intensity increased by 11.6% ( p = 0.017), the Nakagami PDF increased by 72.3% ( p < 0.001), and the Nakagami shape valued increased by 33.0% ( p = 0.028). Conclusions: : Vaginal fibrosis appears to be associated with a thickened vaginal wall, higher echogenicity, as well as increased Nakagami PDF and shape parameters. This pilot study shows the authors' quantitative ultrasound approach combining B‐mode and Nakagami imaging is a promising imaging method to evaluate vaginal fibrosis. This imaging method may be useful as physicians try to address vaginal toxicities and sexual dysfunction in women after radiotherapy for GYN malignancies.